Synthesis and Studies of New Fluorescein‐Porphyrin Dyads: A Theoretical and Experimental Approach. Issue 39 (24th October 2018) - Rezazgui, Olivier; Marchand, Guillaume; Trouillas, Patrick; Siegler, Benjamin; Leroy‐Lhez, Stéphanie
Abstract: Synthesis of two new zinc porphyrin fluorescein dyads are reported here. The two chromophoric units are covalently linked by alkane or alkyne bond, which provides various degrees of flexibility. Conformational analysis as photophysical properties were performed both experimentally (NOESY experiments, lifetimes, ROS production…) and theoretically (DFT and TD‐DFT calculations). Comparison with triazole linker described in a precedent study highlighted that linkage nature determine conformational structure (folding/linearity) but do not significantly modify energy transfer between the two moieties involved in dyads. Abstract : New porphyrin‐fluorescein dyads were synthesized, and relationships between their photophysical properties and conformational features were established. They were thoroughly characterized by a joint theoretical (DFT) and experimental (time‐resolved spectroscopy) approach.